Performance of BER in MIMO-OFDM using QAM and PSK modulation technique with an AWGN channel / Nur Syuhada Mustaffa Kamal - Mustaffa Kamal, Nur Syuhada (2017)
The wireless enviroment introduces a variety challenge to the pysical channel of a communication system, Factors such as multi-path signal reflection, low signal strength and interference can drastically reduce the performance of a receiver. However, the major challenge that needs to face in wireless communication is signal fading, multipath propagation and so on.